Accuracy of Electrocardiography Criteria for Left Ventricular Hypertrophy in Hypertensive Patients at Shahid Gangalal National Heart Centre - Kharel, Sushant; Kadel, Arun; Acharya, Anjana; Neupane, Keshab Raj; Kunwar, Nikosh; KC, Sanjay Singh; Singh, Satish Kumar; Prajapati, Dipanker; Adhikari, Chandra Mani; Rajbhandari, Sujeeb; Rajbhandari, Rajib; Koirala, Umesh; et al. (Nepalese Heart Journal, 2024)
Background: Hypertension is the leading cause of cardiovascular disease and premature death worldwide. Left ventricular hypertrophy (LVH), a measure of hypertensive target organ damage in the heart is associated with increased morbidity, mortality and development of arrhythmias. This study was designed to identify the more accurate ECG criteria for identifying LVH taking LVH by echocardiography as reference. Methods: A cross sectional study was conducted at Shahid Gangalal National Heart Centre. A total of 252 patients were included. A 12-lead ECG and Echocardiography were done. Analysis done by SPSS 25. Stata-14 software was used for ROC (Receiver operating characteristics) comparison and P<0.05 considered statistically significant. Results: Sensitivity, specificity, PPV, NPV and accuracy of Sokolow-Lyon criteria in diagnosis LVH was 41.8%, 80.8%, 67.1%, 59.7% and 61.9% respectively. The results of the test parameters taking Cornell Voltage criteria to detect LVH was 65.6%, 73.1%, 69.6% 69.3% and 69.4%. Likewise, the test parameters of cornell voltage duration measurement was 57.4%, 84.6%, 77.8%, 67.9% and 71.4% respectively. Similarly results of the test parameters by Romhilt-Estes system was 36.9%, 88.5%, 75%, 59.9% and 63.5% respectively. Area under the curve (AUC) of Sokolow-Lyon index, Cornell voltage criteria, Cornell voltage duration measurement and Romhilt- Estes system was 0.613, 0.693, 0.71 and 0.627 respectively. Conclusion: In our study Cornell Voltage duration measurement criteria had a higher sensitivity and higher AUC to detect LVH. The different ECG criteria must be integrated with the clinical scenario. Isolated interpretation of LVH using a single ECG criteria has a low diagnostic value